Immobilization of mushroom polyphenol oxidase on poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) macroporous beaded copolymers - Vaidya, Bhalchandra K.; Karale, Abhijeet J.; Suthar, Hitesh K.; Ingavle, Ganesh C.; Pathak, Tara Sankar; Ponrathnam, S.; Nene, Sanjay (Reactive & Functional Polymers, 2007)
Functional, macroporous, beaded copolymers containing epoxy groups were synthesized for immobilization of polyphenol oxidase (PPO) from edible mushroom (Agaricus bisporus). The effect of incorporation of two different sets of monomers such as glycidyl methacrylate (GMA) and allyl glycidyl ether (AGE) and the effect of cross-linking agent ethylene glycol dimethacrylate (EGDM) with varying cross-link densities on binding and expression of mushroom PPO activity were studied. The effect of porogen viz. cyclohexanol and hexanol on PPO immobilization was studied. AGE copolymers with hexanol as a porogen were found to give higher binding and expression of PPO activity than GE polymers. Crosslinking of amino groups of enzyme with 5% glutaraldehyde for 6 h gave a stable binding of PPO on AGE-75(Hex) polymer with storage half-life of approximately 25 days. Under optimum conditions, AGE-75(Hex) polymer gave 70.3% of activity yield while percent retention of PPO activity was found to be 83.5%. Immobilized PPO showed a broader pH, higher temperature and excellent storage stability. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cross-linking agent; Enzyme immobilization; Epoxy-activated support; mushroom PPO